2021
DOI: 10.3390/ma14030527
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Repeated High Water Pressure on the Compressive and Bond Strength of Concrete with/without Steel Bar

Abstract: The application of reinforced concrete for permanent and temporary deep ocean structures has recently become more prevalent; however, the static and dynamic effects of high water pressure on concrete remain unexplored. This paper investigates the influence of high water pressure (60 MPa) on four series of concrete cylinders with and without an embedded steel bar under sustained and cyclic loading conditions. The residual compressive strength, bond strength, and associated evolution of surface and internal dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Wegen et al 20 conducted uniaxial compression tests on concrete at different hydrostatic pressures and found that water pressure did not adversely affect strength. Muhaimin et al 29 applied a high water pressure of 60 MPa to concrete and found that residual compressive strength decreased significantly. This was a result of the hydraulic gradient caused by the huge difference in internal and external water pressure.…”
Section: Effect Of Water Pressure On Concrete Strengthmentioning
confidence: 99%
See 3 more Smart Citations
“…Wegen et al 20 conducted uniaxial compression tests on concrete at different hydrostatic pressures and found that water pressure did not adversely affect strength. Muhaimin et al 29 applied a high water pressure of 60 MPa to concrete and found that residual compressive strength decreased significantly. This was a result of the hydraulic gradient caused by the huge difference in internal and external water pressure.…”
Section: Effect Of Water Pressure On Concrete Strengthmentioning
confidence: 99%
“…References [7, 8, 11, 12, 17, 18, 20–22, 29, 39–41] were studied on the static strength of concrete after exposure to water pressure. In terms of dynamic strength, Zhou et al 11 used the SHPB device to conduct dynamic mechanical tests on concrete after exposure to different water pressures.…”
Section: Effect Of Water Pressure On Concrete Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Water or an aqueous solution in the pore space has a significant effect on the mechanical properties of concrete. The pore fluid is reported to be responsible for numerous phenomena of premature fracture of various brittle materials (including concretes) under loads significantly lower than permissible for these materials in a dry state [ 6 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%